Unveiling intimacy: sexual dysfunction and marital satisfaction among Pakistani males in Karachi - Yousefzai, Hayat Ali; Ismail, Siti Irma Fadhilah; Hussain, Sana; Alimuddin, Aishah Siddiqah (Oxford University Press, 2025)
Background: In Asian countries, discussing sex-related issues remains a taboo. Sexual dysfunction is not even considered a serious disorder in Pakistan. Aim: To explore sexual dysfunction and marital satisfaction within the Pakistani context to develop supportive intervention programs, Methods: This study entailed a mixed method approach and was carried out in Karachi, Pakistan. The sample comprised 28 married men, and data were gathered by in-depth interviews. Subsequently, data were analyzed through content analysis. Outcomes: There is a strong relationship between marital dissatisfaction and sexual dysfunction in adult married males aged 25 to 40 years in Pakistan. Results: The analysis of participants’ perspectives revealed 5 themes: psychosocial issues, rationale of openness in marital life, insufficient sexual knowledge, lack of sexual health service, and individual consequences. Clinical Implications: The results of this study suggest that it is an important suggestion to the government of Pakistan to introduce sexual health counseling and premarital counseling programs at the university level. The Ministry of Health and Higher Education needs to promote awareness about sexual health, sexual dysfunctions, and marital satisfaction, which will enable men to understand their sexual problems and effectively cope with them. Strengths and Limitations: The different results found in this study shed light on biopsychosocial dimensions of human sexuality. In this study, psychosocial aspects associated with sexual dysfunctions are taboo due to Islamic society, which prevents male partners from openly discussing sexual issues with their female partners due to fear of damaging their marital lives. The limitation of this study is that the sample is not generalized; it is also not a demographic representation of all socioeconomic groups in Pakistan. Participants in low and middle classes reported an inability to seek help from professionals due to the high costs of treatments. Therefore, the results cannot to be extended to all Pakistani males. Conclusion: In this study, male sexual dysfunction strongly affects marital satisfaction within the couple. As such, marital counseling and psychotherapeutic strategies play an important role to help individuals and couples manage their sexual dysfunctions and enhance their marital satisfaction.